Plasma endocannabinoids in cocaine dependence and their relation to cerebral metabotropic glutamate receptor 5 density - Kroll, Sara Liane; Hulka, Lea M.; Kexel, Ann-Kathrin; Vonmoos, Matthias; Preller, Katrin H.; Treyer, Valerie; Ametamey, Simon M.; Baumgartner, Markus R.; Boost, Carola; Pahlisch, Franziska; Rohleder, Cathrin; Leweke, F. Markus; et al. (Translational Psychiatry, 2023)
Animal models indicate that the endocannabinoid system (ECS) plays a modulatory role in stress and reward processing, both crucially impaired in addictive disorders. Preclinical findings showed endocannabinoid-modulated synaptic plasticity in reward brain networks linked to the metabotropic-glutamate-5 receptor (mGluR5), contributing to drug-reinforcing effects and drug-seeking behavior. Although animal models postulate a link between ECS and cocaine addiction, human translational studies are lacking. Here, we tested previous preclinical findings by investigating plasma endocannabinoids (eCBs) anandamide (AEA), 2-arachidonoylglycerol (2-AG), and the related N-acylethanolamines (NAEs) palmitoylethanolamide (PEA) and oleoylethanolamide (OEA), including their interaction with cerebral mGluR5, in chronic cocaine users (CU). We compared basal plasma concentrations between chronic CU (N = 103; 69 recreational CU and 34 dependent CU) and stimulant-naïve healthy controls (N = 92). Follow-up basal eCB/NAE plasma levels after 12 months were used for reliability and stability check (CU: N = 33; controls: N = 43). In an additional analysis using 11C-ABP688 positron emission tomography (PET) in a male subsample (CU: N = 18; controls: N = 16), we investigated the relationships between eCBs/NAEs and mGluR5 density in the brain. We found higher 2-AG plasma levels in dependent CU compared to controls and recreational CU. 2-AG levels were stable over time across all groups. In the PET-subsample, a positive association between 2-AG and mGluR5 brain density only in CU was found. Our results corroborate animal findings suggesting an alteration of the ECS in cocaine dependence and an association between peripheral 2-AG levels and cerebral mGluR5 in humans. Therefore, the ECS might be a promising pharmaco-therapeutic target for novel treatments of cocaine dependence.